LAZZARINI, Isabella, ed. (2021), The Later Middle Ages, Oxford, Oxford University Press. ISBN: 978-0-19-873163-4, 296 pp. - Rodrigues, André (História: revista da Faculdade de Letras da Universidade do Porto, 2022)
Recensão da obra: LAZZARINI, Isabella, ed. (2021), (2021), The Later Middle Ages, Oxford, Oxford University Press. ISBN: 978-0-19-873163-4, 296 pp.